2018
DOI: 10.1016/j.biosystems.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A test of the adaptive network explanation of functional disorders using a machine learning analysis of symptoms

Abstract: The classification and etiology of functional disorders is controversial. Evidence supports both psychological and biological (disease) models that show, respectively, that functional disorders should be classified as one (bodily distress syndrome) and many (e.g., irritable bowel syndrome (IBS), fibromyalgia syndrome (FMS), and chronic fatigue syndrome (CFS)). Two network models (symptom network and adaptive network) can explain the specificity and covariation of symptomatology, but only the adaptive network m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…Network theory suggests that similarity between groups should increase with severity because increased severity is associated with increased pathology over the whole network. Therefore symptom patterns within different diagnostic groups should converge as severity increases, consistent with evidence elsewhere that people diagnosed with IBS or CFS become more similar to the more severe group of FMS as the frequency of IBS and CFS symptoms increases . We found that people reporting a diagnosis of FMS report the most frequent symptoms compared with IBS and CFS (see Table ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Network theory suggests that similarity between groups should increase with severity because increased severity is associated with increased pathology over the whole network. Therefore symptom patterns within different diagnostic groups should converge as severity increases, consistent with evidence elsewhere that people diagnosed with IBS or CFS become more similar to the more severe group of FMS as the frequency of IBS and CFS symptoms increases . We found that people reporting a diagnosis of FMS report the most frequent symptoms compared with IBS and CFS (see Table ).…”
Section: Discussionsupporting
confidence: 88%
“…In a network of mutually activating nodes, increase in one part of the network activates increases activity across the whole network, such that differentiation between the original activating site and elsewhere becomes lost as severity increases. This prediction has been confirmed using a machine learning form of analysis with the additional finding that the connection strengths between the outgoing connections also increased with severity, showing that the underlying network structure (and therefore adaptation) varies with severity …”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations